Pengaruh Kontribusi Penerimaan Pajak Daerah Terhadap Pendapatan Asli Daerah (PAD) - Difu, Julick Ferlis; LALOMA, ALDEN; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2015)
AbstractThis thesis aims to determine the contribution of local tax revenue to PAD who performed theDepartment of Finance and Asset Management District South Halmahera during the three fiscal years(2010-2012) , as well as enabling and inhibiting factors in increasing revenue ( PAD ) in taxes area inSouth Halmahera . The results showed that the contribution of local taxes to large revenuecontribution. This is reflected in the amount of local tax contributions increased from year to year anda source of revenue ( PAD ) District. South Halmahera where we see of the total revenue of Rp .11,735,130,069.82 in 2010 , local taxes accounted for Rp 1,223,577,233.00 or 10.51 % and then in 2011of the total revenue of Rp.32.296.618.479,35, local taxes accounted for Rp 2,333,993,323.00 or 29.93 % ,and in 2012 of the total revenue of Rp.43,965,874,804.28 local taxes accounted for Rp 3,368,905,822.00or 40.59 % .The factors affecting the increase in revenue ( PAD ) of the local tax sector enabling andinhibiting factors . Supporting factors include the organization and management , facilities andinfrastructure as well as the intensification and extension were carried Dpkad Kab . South Halmahera, while the limiting factor is the participation of the community in paying taxes , data collection orcomplicated test , and quality personnel inadequate marked with the level of education that do notcomply with the ability to manage local taxes .Keywords : Local Taxes , Local Revenue